(untitled) - Ahmad Riyadh Umar Bahlamar (Jurnal Caraka Prabu)
The number of patient visits every day is increasing, this incident causes the waiting room to become crowded and crowded because it takes a long time for officers to find the patient's medical record folder and many patients complain if they wait too long. This causes the low quality of service at the registration counter at the Tarik Health Center. From the problems that result in the low quality of service at the Tarik Health Center, an innovation was made to overcome the problem of patient queues in the counter room to facilitate and speed up patient queue services through an application system on Android. The application created by the Tarik Health Center is the Tarik Health Center Queue Information System (SIAP TARIK). This study aims to describe and analyze a level of quality of the SIAP TARIK application system in improving the registration counter queue service at the Tarik Health Center. This study uses a bibliometric analysis method using two main sources, Google Scholar and also publish or perish. Which uses the keywords empathy, service quality, innovation, public service, e- government, quality, public, smart card, Siap Tarik application. Publish or Perish (PoP) application to generate data from 2020 – 2023 mentioned sources. The data obtained is then analyzed, and displayed using VOSViewer. VOS viewer is a useful software for building and visualizing.